Pezizomycetes genomes reveal the molecular basis of ectomycorrhizal truffle lifestyle. Issue 12 (December 2018) - Murat, Claude; Payen, Thibaut; Noel, Benjamin; Kuo, Alan; Morin, Emmanuelle; Chen, Juan; Kohler, Annegret; Krizsán, Krisztina; Balestrini, Raffaella; Silva, Corinne; Montanini, Barbara; Hainaut, Mathieu; et al.
Abstract Tuberaceae is one of the most diverse lineages of symbiotic truffle-forming fungi. To understand the molecular underpinning of the ectomycorrhizal truffle lifestyle, we compared the genomes of Piedmont white truffle (Tuber magnatum ), Périgord black truffle (Tuber melanosporum ), Burgundy truffle (Tuber aestivum ), pig truffle (Choiromyces venosus ) and desert truffle (Terfezia boudieri ) to saprotrophic Pezizomycetes. Reconstructed gene duplication/loss histories along a time-calibrated phylogeny of Ascomycetes revealed that Tuberaceae-specific traits may be related to a higher gene diversification rate. Genomic features inTuber species appear to be very similar, with high transposon content, few genes coding lignocellulose-degrading enzymes, a substantial set of lineage-specific fruiting-body-upregulated genes and high expression of genes involved in volatile organic compound metabolism. Developmental and metabolic pathways expressed in ectomycorrhizae and fruiting bodies ofT. magnatum andT. melanosporum are unexpectedly very similar, owing to the fact that they diverged 100 Ma. Volatile organic compounds from pungent truffle odours are not the products ofTuber -specific gene innovations, but rely on the differential expression of an existing gene repertoire. These genomic resources will help to address fundamental questions in the evolution of the truffle lifestyle and the ecology of fungi that have been praised as food delicacies for centuries. Genomes of three Tuberaceae species and two related truffle species reveal genetic similarities across symbiotic truffle-forming fungi, including high expression of genes involved in volatile organic compound metabolism.